Implementasi Metode FMEA untuk Mereduksi Cacat Produk pada Proses Produksi Sandal di Departemen Plong - Amiruddin, Mochamad; Abdul Wahid (Jurnal Serambi Engineering, 2025)
CV. Bossbi, as one of the sandal manufacturers, faces challenges related to defective products originating from the initial production process. This study aims to implement the Failure Mode and Effect Analysis (FMEA) method to identify, analyze, and prioritize corrective actions to reduce product defects in the Plong Department. This study uses a quantitative descriptive approach with data collection for two months (January-February 2025) through observation and interviews. The results of the study identified three dominant types of defects from a total production of 177,990 pairs of sandals, namely asymmetrical patterns (39.95%), uneven edges (31.14%), and inappropriate sizes (28.92%). The FMEA analysis produces a Risk Priority Number (RPN) value for each failure mode, where 'asymmetrical patterns' obtained the highest RPN value of 224, followed by 'inappropriate sizes' (RPN = 189), and 'uneven edges' (RPN = 175). The highest RPN value indicates that 'asymmetrical pattern' is the most critical risk caused by imprecise material placement and rushed operators. Based on these priorities, it is recommended that corrective actions be taken in the form of making jigs (assistive tools), standardizing operational procedures (SOPs), and scheduling regular machine maintenance. The implementation of FMEA has proven effective as a tool for mapping risks and providing a basis for measurable improvement proposals to significantly improve product quality.